Studying Shelf Framing With Multiple Consumer Insights - Enrique Strelow; Verena Hauschildt; Mark Heitmann; Christian Scheier (Marketing Review St.Gallen, 2017)
Sustaining competitive advantage requires continuous innovations. In times of saturated markets, successful new product launches are increasingly challenging. This is evidenced by high failure rates. For example, GfK (2015) reports less than a third of new products survived beyond two years in FMCG. Diminishing such staggering failure rates has become a chief concern for many marketers. Two critical product launch decisions involve advertising positioning and distribution placement.
Keywords: 650